ALGUNOS EJEMPLOS DE BUENAS PRACTICAS DE LA UTILIZACIÓN DE LA INTELIGENCIA ARTIFICIAL EN LA GESTIÓN DE SERVICIOS PÚBLICOS - LAURA ALVAREZ GARCIA (Revista Vasca de Gestión de Personas y Organizaciones Públicas)
Two of the major problems facing local authorities (hereinafter RLE) are the provision of mandatory public services, due to the configuration of the municipal system, the small-scale farming and the acute depopulation of rural areas. To alleviate the problems of the municipal system and provide public services, there are various alternatives: administra-tive cooperation; the provision of services by provincial councils, Cabildos and Councils; the implementation of associative formulas such as associations of municipalities. At the present, we must highlight the experiencesthat the Administration is having with tools based on artificial intelligence (hereinafter, AI). By analyzing various use cases, we will see how using AI-based tools improves the processing of administrative files from the two sides of RLE: the front office, with special reference to the provision of mandatory ser-vices, boosting their quality, reducing their cost, and increasing their efficiency; and the back office, implementing AI tools to streamline and automate administrative procedures.